Analysis of Beliefs and Confidence Regarding Osteoporosis Among Nurses Working in Orthopedic Department - Bano, Shakeela; Parveen, Samina; Ali, Adeeba (Biological and Clinical Sciences Research Journal, 2025)
Osteoporosis is a major global health concern, particularly in ageing populations. Nurses play a pivotal role in patient education and preventive care, making their health beliefs and self-efficacy regarding osteoporosis crucial in promoting effective prevention strategies. Understanding orthopaedic nurses’ perceptions and confidence in managing osteoporosis can inform targeted educational interventions to enhance patient care. Methods: A cross-sectional analysis of 100 nurses working in the Orthopedic Department of Nishtar Hospital, Multan was conducted from January 2024 to January 2025. Inclusion criteria were registered nurses working full-time in the department. All participants were presented a self-reported questionnaire divided into three sections; sociodemographic data, Osteoporosis Health Belief Scale, and Self-efficacy. Results: The overall health beliefs score was 123.5 ± 13.66 with a moderately high score for advantage of exercise (20.53 ± 4.33) and health motivation (21.25 ± 4.11). While the susceptibility score (17.08 ± 5.28), seriousness for osteoporosis (16.70 ± 4.1), barriers to exercise (14.98 ± 3.75), and calcium intake (13.18 ± 3.93) had moderately low scores. Participants had a neutral score for the advantages of calcium intake (19.87 ± 3.7). The overall self-efficacy score was 71.97 ± 24.44 which was a moderately high score. The score for exercise was 31.48 ± 12.56 and for calcium consumption, it was 40.49 ± 11.88. Conclusion: The orthopaedic nurses had a moderately high self-efficacy and satisfactory health beliefs which highlight the importance and need for educational programs to educate nurses.